A basalt fiber toughened by zirconium oxide phase change and its preparation method
By adding zirconia phase transformation toughening materials and inorganic reinforcement whiskers to basalt fibers, and using ball mill mixing and ultrasonic dispersion processes, the problem of insufficient strength of existing basalt fibers is solved, significantly improving its tensile strength and tensile elastic modulus, meeting the technical needs of emerging fields.
Patent Information
- Application Number
- CN202410395420.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-04-02
AI Technical Summary
The strength requirements of existing basalt fibers in emerging fields cannot be met, and new technologies and processes are urgently needed to improve their strength.
By adding zirconia phase transformation toughening materials and inorganic reinforcement whiskers to basalt fibers, ball mill mixing and ultrasonic dispersion processes are used to improve the fracture toughness and mechanical properties of the fibers.
The tensile strength and tensile elastic modulus of basalt fibers have been significantly improved, and meet the performance index requirements of high-strength and high-modulus basalt fibers in GB/T 38111-2019.
Smart Images

Figure BDA0004773849870000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of high-performance inorganic fiber materials, and in particular to a basalt fiber toughened by zirconium oxide phase change and a preparation method thereof. Background Art
[0002] Basalt fiber is a high-performance inorganic fiber made by rapidly drawing basalt stone through a leaky plate after melting it at high temperature. It has excellent physical and chemical properties such as temperature resistance, single-filament mechanical strength, elastic modulus, density, creep rupture stress, chemical stability, and corrosion resistance is better than that of ordinary glass fiber. At the same time, it produces less waste in the production process, and the product will not pollute the environment after being discarded, and there is no harm, so it is a veritable green and environmentally friendly material. At present, basalt fiber has been used in many fields such as national defense and military industry, civil construction facilities, building reinforcement, marine engineering, ultra-high voltage power transmission, rail transit vehicles, automobile lightweighting, fire protection, and environmental protection.
[0003] However, many emerging fields have further increased their demands for the strength of fiber materials. At the same time, the performance of basalt fiber based on the current production process cannot meet the new requirements. It is urgent to develop new technologies and processes to improve the strength of basalt fiber to adapt to the technological development of emerging fields. Summary of the invention
[0004] In view of the problems and shortcomings of the prior art, the present invention provides a basalt fiber toughened by zirconium oxide phase change and a preparation method thereof.
[0005] Based on the above purpose, the present invention adopts the following technical solution:
[0006] In a first aspect, the present invention provides a basalt fiber based on zirconium oxide phase change toughening, which comprises, by weight: 100 parts of basalt, 5 to 10 parts of phase change toughening material, and 0.5 to 1.5 parts of inorganic reinforcing whiskers.
[0007] Preferably, the basalt comprises the following chemical components: SiO2+Al2O369%-83%, Fe x O y 10%~15%, CaO+MgO 5%~10%, NaO+K2O 2%~5%, others 0%~1%.
[0008] Preferably, the phase change toughening material comprises the following components in parts by mass: 100 parts of metal oxide carrier, 5-10 parts of nano zirconium oxide, and 1-2 parts of grinding aid.
[0009] More preferably, the metal oxide carrier is at least one of calcium oxide (CaO), magnesium oxide (MgO), cerium oxide (CeO2), and yttrium oxide (Y2O3), and has an average particle size of 1 to 10 μm.
[0010] More preferably, the nano zirconium oxide is tetragonal nano zirconium oxide doped with yttrium oxide, wherein the mass fraction of yttrium oxide is 4% to 8%.
[0011] More preferably, the average particle size of the nano zirconium oxide is 10 to 100 nm.
[0012] More preferably, the grinding aid is at least one of sodium hexametaphosphate, sodium tripolyphosphate and sodium polyacrylate.
[0013] Furthermore, the phase change toughening material is prepared by the following method: a metal oxide carrier, nano zirconium oxide and a grinding aid are mixed by ball milling.
[0014] Furthermore, the ball milling medium is alumina ceramic balls.
[0015] Furthermore, the ball milling speed is 200-400 r / min, and the duration is 30-60 min.
[0016] Preferably, the inorganic reinforcing whisker is at least one of zirconium oxide whisker, boron nitride whisker and silicon carbide whisker.
[0017] Preferably, the inorganic reinforcing whisker has a diameter of 0.1-3 μm and an aspect ratio of 20-100.
[0018] In a second aspect, the present invention provides a method for preparing basalt fiber toughened by zirconium oxide phase change, comprising the following steps:
[0019] (1) ball-milling the metal oxide carrier, nano zirconium oxide, and a grinding aid to obtain a phase change toughening material;
[0020] (2) crushing, grinding, and sieving the basalt, heating it to melt it, and keeping it warm to obtain a basalt melt, adding a phase change toughening material to the basalt melt, ultrasonically dispersing it, and then cooling it, and then adding an inorganic reinforcing whisker and ultrasonically dispersing it to obtain a mixed melt;
[0021] (3) The mixed molten liquid is drawn to obtain a basalt fiber toughened by zirconium oxide phase change.
[0022] Furthermore, in the screening process in step (2), a 100-mesh square hole sieve is used.
[0023] Furthermore, the heating temperature in step (2) is 1500°C to 1700°C.
[0024] Furthermore, the insulation time in step (2) is 1 to 2 hours.
[0025] Furthermore, in step (2), the first ultrasonic dispersion time is 30 to 60 minutes, the second ultrasonic dispersion time is 20 to 40 minutes, and the frequencies of both ultrasonic dispersions are 20 KHz to 80 KHz.
[0026] Furthermore, the cooling temperature in step (2) is to be between 1400°C and 1500°C.
[0027] Furthermore, the wire drawing speed in step (3) is 4 to 8 m / s.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention adds phase change toughening materials to basalt fibers, wherein tetragonal nano zirconium oxide particles can improve the fracture toughness of fibers through stress-induced phase change toughening and other mechanisms when microcracks occur in the fibers, thereby improving the tensile strength and tensile elastic modulus of the basalt fibers; metal oxides are used as carriers of phase change toughening materials to reduce the agglomeration of nano zirconium oxide in basalt melt, thereby obtaining a uniformly dispersed melt and further improving the mechanical properties of basalt fibers, especially when metal oxides such as CaO, MgO, CeO2, and Y2O3 are used, which can better infiltrate the nano zirconium oxide.
[0030] 2. The present invention adds inorganic reinforcing whiskers to basalt fibers and distributes them evenly in the basalt melt by ultrasonic dispersion. After drawing, the whiskers can slow down the development of the crack tip inside the fiber through the bridging mechanism and the crack deflection mechanism, thereby improving the fracture toughness of the basalt fibers.
[0031] 3. The basalt fiber based on zirconium oxide phase change toughening provided by the present invention has better tensile strength and tensile elastic modulus. Under the joint action of phase change toughening material and inorganic reinforcing whiskers, the tensile strength of the basalt fiber is as high as 4525MPa, and the tensile elastic modulus is as high as 107GPa, which meets the performance index requirements of high-strength and high-modulus basalt fiber in GB / T 38111-2019. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail by examples below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] Example 1
[0034] A basalt fiber based on zirconium oxide phase change toughening comprises the following components by weight: 100 parts of basalt, 7 parts of phase change toughening material, and 1 part of inorganic reinforcing whisker (with a diameter of 1 μm and an aspect ratio of 30).
[0035] The above-mentioned method for preparing basalt fiber based on zirconium oxide phase change toughening comprises the following steps:
[0036] (1) 100 parts of magnesium oxide (average particle size of 6 μm), 7 parts of nano zirconium oxide (average particle size of 50 nm, Y2O3 mass fraction of 6%), and 1.5 parts of sodium tripolyphosphate were ball-milled, the ball-milling medium was alumina ceramic balls, the rotation speed was 300 r / min, and the time was 45 min to obtain a phase change toughened material.
[0037] (2) 100 parts of basalt (chemical composition: SiO2+Al2O375%, Fe x O y 12%, CaO+MgO 8.5%, NaO+K2O 4%, others 0.5%) were crushed and ground, passed through a 100-mesh square hole sieve, heated to 1600°C to melt it and kept warm for 1.5 hours to obtain a basalt melt, 7 parts of phase change toughening material were added to the basalt melt, ultrasonically dispersed for 45 minutes at a frequency of 40KHz, then cooled to 1450°C, 1 part of zirconia whisker was added, and ultrasonically dispersed for 20 minutes at a frequency of 40KHz to obtain a mixed melt.
[0038] (3) The mixed molten liquid is drawn at a drawing speed of 6 m / s to obtain a basalt fiber toughened by zirconium oxide phase transformation.
[0039] Comparative Example 1
[0040] A basalt fiber, the preparation method comprises the following steps:
[0041] (1) 100 parts of basalt (chemical composition: SiO2+Al2O375%, Fe x O y 12%, CaO+MgO 8.5%, NaO+K2O 4%, others 0.5%) were crushed and ground, passed through a 100-mesh square-hole sieve, heated to 1600°C to melt and kept warm for 1.5 hours to obtain basalt melt.
[0042] (2) The basalt melt is drawn at a drawing speed of 6 m / s to obtain a basalt fiber.
[0043] The performance of the basalt fibers prepared in Example 1 and Comparative Example 1 was tested according to the test method described in GB / T 20310-2006 “Preparation of Glass Fiber Roving Dipped Yarn Samples and Determination of Tensile Strength”. The results are shown in Table 1.
[0044] Table 1 Effect of toughening modification on the properties of basalt fiber
[0045] Group Whether toughening modification Tensile strength / MPa Tensile elastic modulus / GPa Example 1 yes 4525 107 Comparative Example 1 no 2717 85
[0046] It can be seen from Table 1 that in Comparative Example 1, the tensile strength and tensile elastic modulus of the basalt fiber are lower than those of the basalt fiber in Example 1, indicating that after the basalt fiber is toughened and modified by the toughening material and process used in the present invention, the tensile strength and tensile elastic modulus of the basalt fiber are significantly improved.
[0047] Example 2
[0048] A basalt fiber based on zirconium oxide phase change toughening, whose composition and preparation method are basically the same as those of Example 1, except that the amount of phase change toughening material used is 5 parts.
[0049] Example 3
[0050] A basalt fiber based on zirconium oxide phase change toughening, whose composition and preparation method are basically the same as those of Example 1, except that the amount of phase change toughening material used is 10 parts.
[0051] Comparative Example 2
[0052] A basalt fiber based on zirconium oxide phase change toughening, whose composition and preparation method are basically the same as those of Example 1, except that no phase change toughening material is added.
[0053] The performance of the basalt fibers prepared in Examples 2 to 3 and Comparative Example 2 was tested according to the test method described in GB / T 20310-2006 “Preparation of Glass Fiber Roving Dipped Yarn Samples and Determination of Tensile Strength”. The results are shown in Table 2.
[0054] Table 2 Effect of the amount of phase change toughening material on the properties of basalt fiber
[0055] Group Phase change toughening material dosage (parts by mass) Tensile strength / MPa Tensile elastic modulus / GPa Example 1 7 4525 107 Example 2 5 4408 98 Example 3 10 4517 101 Comparative Example 2 0 3309 88
[0056] It can be seen from Table 2 that in Comparative Example 2, the basalt fiber without adding phase change toughening material has a lower tensile strength and tensile elastic modulus than the basalt fibers in other embodiments. Among them, when the amount of phase change toughening material used in Example 1 is 7 parts by mass, the tensile strength and tensile elastic modulus of the basalt fiber are higher than those in other embodiments.
[0057] Example 4
[0058] A basalt fiber based on zirconium oxide phase change toughening, whose composition and preparation method are basically the same as those of Example 1, except that the metal oxide carrier in the phase change toughening material is calcium oxide.
[0059] Example 5
[0060] A basalt fiber based on zirconium oxide phase change toughening, whose composition and preparation method are basically the same as those of Example 1, except that the metal oxide carrier in the phase change toughening material is cerium oxide.
[0061] Example 6
[0062] A basalt fiber based on zirconium oxide phase change toughening, whose composition and preparation method are basically the same as those of Example 1, except that the metal oxide carrier in the phase change toughening material is calcium oxide and yttrium oxide mixed in a mass ratio of 4:1.
[0063] The performance of the basalt fibers prepared in Examples 4 to 6 was tested according to the test method described in GB / T 20310-2006 “Preparation of Glass Fiber Roving Dipped Yarn Samples and Determination of Tensile Strength”. The results are shown in Table 3.
[0064] Table 3 Effect of metal oxide carrier types in phase change toughening materials on the properties of basalt fibers
[0065] Group Metal oxide support type Tensile strength / MPa Tensile elastic modulus / GPa Example 1 Magnesium Oxide 4525 107 Example 4 Calcium Oxide 4309 96 Example 5 Cerium Oxide 4454 99 Example 6 Calcium oxide and yttrium oxide are mixed in a mass ratio of 4:1 4478 103
[0066] It can be seen from Table 3 that in Example 1, when the metal oxide carrier in the phase change toughening material is magnesium oxide, its tensile strength and tensile elastic modulus are higher than those of other examples.
[0067] Example 7
[0068] A basalt fiber based on zirconium oxide phase change toughening, whose composition and preparation method are basically the same as those of Example 1, except that the amount of nano zirconium oxide in the phase change toughening material is 5 parts.
[0069] Example 8
[0070] A basalt fiber based on zirconium oxide phase change toughening, whose composition and preparation method are basically the same as those of Example 1, except that the amount of nano zirconium oxide in the phase change toughening material is 10 parts.
[0071] Comparative Example 3
[0072] A basalt fiber based on zirconium oxide phase change toughening, whose composition and preparation method are basically the same as those of Example 1, except that nano zirconium oxide is not added to the phase change toughening material.
[0073] The performance of the basalt fibers prepared in Examples 7 to 8 and Comparative Example 3 was tested according to the test method described in GB / T 20310-2006 “Preparation of Glass Fiber Roving Dipped Yarn Samples and Determination of Tensile Strength”. The results are shown in Table 4.
[0074] Table 4 Effect of the amount of nano-zirconia in phase change toughening materials on the properties of basalt fibers
[0075] Group Nano-zirconia dosage (parts by mass) Tensile strength / MPa Tensile elastic modulus / GPa Example 1 7 4525 107 Example 7 5 4436 96 Example 8 10 4502 103 Comparative Example 3 0 3419 90
[0076] It can be seen from Table 4 that in Comparative Example 3, nano zirconium oxide is not added to the phase change toughening material, and its tensile strength and tensile elastic modulus are both lower than those of the basalt fiber in other embodiments. Among them, when the amount of nano zirconium oxide in the phase change toughening material in Example 1 is 7 parts by mass, the tensile strength and tensile elastic modulus of the basalt fiber are higher than those in other embodiments.
[0077] Example 9
[0078] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those of Example 1, except that the mass fraction of Y2O3 in the nano zirconium oxide is 4%.
[0079] Example 10
[0080] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those of Example 1, except that the mass fraction of Y2O3 in the nano zirconium oxide is 8%.
[0081] The performance of the basalt fibers prepared in Examples 9 to 10 was tested according to the test method described in GB / T 20310-2006 “Preparation of Glass Fiber Roving Dipped Yarn Samples and Determination of Tensile Strength”. The results are shown in Table 5.
[0082] Table 5 Effect of Y2O3 mass fraction in nano-zirconia on the properties of basalt fiber
[0083] Group <![CDATA[Mass fraction of Y2O3 content]]> Tensile strength / MPa Tensile elastic modulus / GPa Example 1 6% 4525 107 Example 9 4% 4378 98 Example 10 8% 4476 102
[0084] It can be seen from Table 5 that in Example 1, when the mass fraction of Y2O3 in the nano-zirconia is 6%, its tensile strength and tensile elastic modulus are higher than those of other examples.
[0085] Embodiment 11
[0086] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those of Example 1, except that the amount of inorganic reinforcing whisker used is 0.5 parts.
[0087] Example 12
[0088] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those of Example 1, except that the amount of inorganic reinforcing whisker used is 1.5 parts.
[0089] Comparative Example 4
[0090] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those of Example 1, except that no inorganic reinforcing whiskers are added.
[0091] The performance of the basalt fibers prepared in Examples 11 to 12 and Comparative Example 4 was tested according to the test method described in GB / T 20310-2006 “Preparation of Glass Fiber Roving Dipped Yarn Samples and Determination of Tensile Strength”. The results are shown in Table 6.
[0092] Table 6 Effect of the amount of inorganic reinforcing whiskers on the properties of basalt fibers
[0093] Group Inorganic reinforcing whisker dosage (parts by mass) Tensile strength / MPa Tensile elastic modulus / GPa Example 1 1 4525 107 Embodiment 11 0.5 4366 95 Example 12 1.5 4445 98 Comparative Example 4 0 4059 94
[0094] It can be seen from Table 6 that in Example 1, when the amount of inorganic reinforcing whisker is 1 part by mass, its tensile strength and tensile elastic modulus are higher than those of other examples.
[0095] Embodiment 13
[0096] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those of Example 1, except that the inorganic reinforcing whisker is boron nitride whisker.
[0097] Embodiment 14
[0098] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those of Example 1, except that the inorganic reinforcing whisker is silicon carbide whisker.
[0099] The performance of the basalt fibers prepared in Examples 13 to 14 was tested according to the test method described in GB / T 20310-2006 “Preparation of Glass Fiber Roving Dipped Yarn Samples and Determination of Tensile Strength”. The results are shown in Table 7.
[0100] Table 7 Effect of inorganic reinforcing whisker types on basalt fiber properties
[0101] Group Inorganic reinforced whisker types Tensile strength / MPa Tensile elastic modulus / GPa Example 1 Zirconia Whiskers 4525 107 Example 13 Boron Nitride Whiskers 4452 102 Embodiment 14 Silicon Carbide Whiskers 4479 101
[0102] It can be seen from Table 7 that in Example 1, when the inorganic reinforcing whiskers are zirconium oxide whiskers, the tensile strength and tensile elastic modulus are higher than those of other examples.
[0103] Embodiment 15
[0104] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those of Example 1, except that in step (2), the heating temperature is 1500°C and the cooling temperature is 1400°C.
[0105] Example 16
[0106] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those of Example 1, except that in step (2), the heating temperature is 1700°C and the cooling temperature is 1500°C.
[0107] The performance of the basalt fibers prepared in Examples 15 to 16 was tested according to the test method described in GB / T 20310-2006 “Preparation of Glass Fiber Roving Dipped Yarn Samples and Determination of Tensile Strength”. The results are shown in Table 8.
[0108] Table 8 Effect of temperature regime on basalt fiber properties
[0109] Group Temperature regime Tensile strength / MPa Tensile elastic modulus / GPa Example 1 Heating temperature 1600℃, cooling temperature 1450℃ 4525 107 Embodiment 15 Heating temperature 1500℃, cooling temperature 1400℃ 4473 100 Example 16 Heating temperature 1700℃, cooling temperature 1500℃ 4411 102
[0110] It can be seen from Table 8 that in Example 1, when the heating temperature in step (2) is 1600°C and the cooling temperature is 1450°C, the tensile strength and tensile elastic modulus are higher than those of other examples.
[0111] Embodiment 17
[0112] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those in Example 1, except that in step (3), the drawing speed is 4 m / s.
[0113] Embodiment 18
[0114] A basalt fiber toughened by zirconium oxide phase change, whose composition and preparation method are basically the same as those in Example 1, except that in step (3), the drawing speed is 8 m / s.
[0115] The performance of the basalt fibers prepared in Examples 17 to 18 was tested according to the test method described in GB / T 20310-2006 “Preparation of Glass Fiber Roving Dipped Yarn Samples and Determination of Tensile Strength”. The results are shown in Table 9.
[0116] Table 9 Effect of drawing speed on basalt fiber properties
[0117]
[0118]
[0119] It can be seen from Table 9 that in Example 1, when the drawing speed in step (3) is 6 m / s, its tensile strength and tensile elastic modulus are higher than those of other embodiments.
[0120] It can be seen from Tables 1 to 9 that the basalt fiber toughened by zirconium oxide phase change prepared in the present invention exhibits higher tensile strength and tensile elastic modulus. The basalt fiber prepared in Example 1 has a tensile strength of up to 4525 MPa and a tensile elastic modulus of up to 107 GPa, which meets the performance index requirements of high-strength and high-modulus basalt fibers in GB / T 38111-2019.
[0121] The above is a description of a preferred embodiment of the present invention, but it should be understood that the invention is not limited to the contents disclosed herein. As long as non-substantial improvements are made using the method concept and technical solution of the present invention, or the method concept and technical solution of the present invention are applied to other occasions, they are all within the scope of protection of the present invention.
Claims
1. A basalt fiber toughened by zirconium oxide phase change, characterized in that: The composition includes the following components by weight: 100 parts of basalt, 5 to 10 parts of phase change toughening material, and 0.5 to 1.5 parts of inorganic reinforcing whisker; The phase change toughening material comprises the following components by mass: 100 parts of a metal oxide carrier, 5 to 10 parts of nano zirconium oxide, and 1 to 2 parts of a grinding aid; the metal oxide carrier is at least one of calcium oxide, magnesium oxide, cerium oxide, and yttrium oxide, and has an average particle size of 1 to 10 μm; the inorganic reinforcing whisker is at least one of zirconium oxide whisker, boron nitride whisker, and silicon carbide whisker; the nano zirconium oxide is a tetragonal nano zirconium oxide doped with yttrium oxide, wherein the mass fraction of yttrium oxide is 4% to 8%.
2. The basalt fiber toughened by zirconium oxide phase change according to claim 1, characterized in that: The inorganic reinforced whisker has a diameter of 0.1-3 μm and an aspect ratio of 20-100.
3. The method for preparing basalt fiber toughened by zirconium oxide phase change according to claim 1 or 2, characterized in that: The following steps are involved: (1) The metal oxide carrier, nano zirconium oxide and grinding aid are ball-milled to obtain a phase change toughening material; (2) crushing, grinding, and sieving the basalt, heating it to melt it, and keeping it warm to obtain a basalt melt, adding a phase change toughening material to the basalt melt, ultrasonically dispersing it, and then cooling it, and then adding an inorganic reinforcing whisker and ultrasonically dispersing it to obtain a mixed melt; (3) The mixed molten liquid is drawn to obtain a basalt fiber toughened by zirconium oxide phase transformation.
4. The method for preparing basalt fiber toughened by zirconium oxide phase change according to claim 3, characterized in that: The inorganic reinforcing whisker in step (2) is at least one of zirconium oxide whisker, boron nitride whisker and silicon carbide whisker.
5. The method for preparing basalt fiber toughened by zirconium oxide phase change according to claim 4, characterized in that: In step (2), the heating temperature is set to 1500°C to 1700°C, and the cooling temperature is set to 1400°C to 1500°C.
6. The method for preparing basalt fiber toughened by zirconium oxide phase change according to claim 3, characterized in that: The wire drawing speed in step (3) is 4-8 m / s.
Citation Information
Patent Citations
Preparation method of porous basalt fibers
CN105506782A
Method capable of improving high temperature resistance of basalt fiber through surface modification
CN108929049A